Costs associated with obesity in Kazakhstan - Kosherova, Zhanar (Nazarbayev University School of Medicine, 2018)
The aim of this study is to estimate direct medical costs attributable to obesity in Kazakhstan from the governmental perspective for 2008, 2020 and 2030. Cost-of-illness prevalence-based approach was used to estimate the medical direct costs including hospital care, drugs, physician and nursing care covered by the government. There are three types of data required for this study including the actual and predicted estimates of prevalence of the obesity in Kazakhstan for 2008, 2020 and 2030, relative risks for IHD, stroke and T2D and costs on specific disease treatment. All the required information was taken from the secondary data. Thus, the main formula includes multiplying Population Attributable Fraction by the costs for diseases’ treatment.
Keywords: OBESITY; overweight; Kazakhstan; cost; cost of illness